Legal Reasoning of Distribution of Property by Grant Vis A Vis Inheritance Perspective Maslahah Mursalah - bt Abdul Rahman, Waheeda; Aziz, Abdul; Maksum, Ghufron (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2024)
Abstract This study aims to explore legal reasoning in the context of the distribution of property by grant in relation to inheritance from the perspective of maslahah mursalah. Maslahah mursalah is a concept in Islamic law that refers to the permissible public interest, which is the basis for making decisions in situations not directly regulated by Islamic law. This study uses a qualitative approach with descriptive and normative analysis. Data for this study were obtained from primary legal sources such as the Quran, Hadith, and the Compilation of Islamic Law, as well as secondary legal sources that include books and related research reports. The maslahah mursalah theory approach is used as an analytical framework to understand grant practices in the context of inheritance distribution. The results showed that the practice of grants in the distribution of inheritance can be analyzed using the concept of maslahah mursalah. This approach makes it possible to assess whether the distribution of grants is beneficial in general and in accordance with Islamic values. In this context, a deep understanding of the principles of Islamic law related to grants and inheritance is essential to ensure the distribution of inheritance is done fairly and in accordance with religious teachings. This research makes an important contribution to the understanding of how grant practices can be a legitimate and beneficial alternative to the distribution of inheritance in Muslim societies. Keywords: grant; inheritance; maslahah mursalah